2009
DOI: 10.1038/cdd.2009.90
|View full text |Cite
|
Sign up to set email alerts
|

αNAC depletion as an initiator of ER stress-induced apoptosis in hypoxia

Abstract: Accumulation of unfolded proteins triggers endoplasmic reticulum (ER) stress and is considered a part of the cellular responses to hypoxia. The nascent polypeptide-associated complex (NAC) participates in the proper maturation of newly synthesized proteins. However, thus far, there have been no comprehensive studies on NAC involvement in hypoxic stress. Here, we show that hypoxia activates glycogen synthase kinase-3b (GSK-3b) and that the activated GSK-3b destabilizes aNAC with the subsequent apoptosis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 48 publications
3
47
0
Order By: Relevance
“…In mammals, NACA deficiency can cause ER stress and consequently the UPR, which, depending on the context, can trigger apoptosis 25,29 . We found that NACA deficiency does trigger the UPR in zebrafish larvae, and that treatment of naca mutants with the chemical chaperon 4-PBA significantly suppressed SRC apoptosis, and restored CHT haematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, NACA deficiency can cause ER stress and consequently the UPR, which, depending on the context, can trigger apoptosis 25,29 . We found that NACA deficiency does trigger the UPR in zebrafish larvae, and that treatment of naca mutants with the chemical chaperon 4-PBA significantly suppressed SRC apoptosis, and restored CHT haematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that NACA depletion can cause ER stress and ER stress-induced apoptosis through activation of the unfolded protein response (UPR) pathway in mammalian cultured cells 25 . We therefore analysed the expression of seven UPR-related genes in sibling and mutant larvae at 3.5 d.p.f.…”
Section: Articlementioning
confidence: 99%
“…Several secondary consequences of dystrophin deficiency, namely calcium dysregulation, hypoxia/ischaemia and oxidative stress, are causes of endoplasmic reticulum (ER) stress, a condition in which normal ER function is disrupted (9)(10)(11)(12)(13)(14)(15). During ER stress, unfolded and misfolded proteins accumulate in the ER lumen, triggering a set of signalling pathways termed the unfolded protein response (UPR).…”
Section: Introductionmentioning
confidence: 99%
“…Six differential proteins were identified by LC-MS/MS coupled to bioinformatics pattern discovery to predict treatment outcome, including five proteins having higher expression and the other one lower expression in patients with resistant tumor. Some of the identified proteins with differential expression are structural proteins (TMC5B and GFAP), and others are regulatory proteins of cell apoptosis (POTE E) and signal transcription (TXLNG) [12][13][14][15]. We do believe that informative molecules originating from tumor cells or their microenvironment may indeed be present in biological fluids and that their identification may lead to the discovery of potential new biomarkers.…”
Section: Discussionmentioning
confidence: 99%